Pengaruh Antara Internalizing and Externalizing Behavior dan Social Acceptance Terhadap Student Subjective Well-Being - Yurika Octavia; Asri Mutiara Putri; Elsy Junilia (Program Studi Psikologi Islam, 2025)
This study aims to examine the influence of internalizing and externalizing behaviors, along with social acceptance, on student subjective well-being (SSWB) among high school students in Bandar Lampung. SSWB refers to students' perceptions of their quality of life at school, which includes four aspects: school connectedness, academic efficacy, joy of learning, and educational purpose. This research employed a quantitative correlational design involving 188 students selected using a quota sampling method from two accredited private high schools. The instruments used were the Student Subjective Well-Being Questionnaire (SSWQ), Youth Internalizing Externalizing Problems Screener (YIEPS), and Perceived Acceptance Scale (PAS). Multiple linear regression analysis revealed that internalizing and externalizing behaviors had a significant negative effect on SSWB, while social acceptance had a significant positive effect. Collectively, these three variables contributed 9.4% to the variation in SSWB. These findings underscore the importance of emotional regulation and peer support in enhancing students’ well-being at school. Keywords: internalizing, externalizing, behavior, student